A re-evaluation study and literature review on AD8 as a screening tool for dementia - Cho-Hsiang Yang; Yi-Ting Lin; Ming H. Hsieh; Tzung-Jeng Hwang (PLoS ONE, 2025)
Background The Eight-Item Informant Interview to Differentiate Aging and Dementia (AD8) was developed as a screening tool for dementia, with a cutoff score of 2 suggested by the initial study. However, various studies have reported different cutoff values, and many have found that a cutoff of 2 may result in a high false positive rate. Furthermore, a high false positive rate has repeatedly been shown when the AD8 is self-administered in local government screening programs in Taiwan. Objectives This study aimed to test the AD8’s performance, define its best cutoff value, review factors that may affect its performance, and reconsider its role in clinical practice. Methods We recruited 118 participant-informant dyads from a university teaching hospital. For each informant, the AD8 was administered before the Clinical Dementia Rating (CDR) to minimize recall bias. Two geriatric psychiatrists made a consensus clinical diagnosis for each participant based on the DSM-5 criteria. Receiver operating characteristic analysis was used to assess the performance of the AD8. Results Thirty-seven participants had a CDR of 0, 61 had a CDR of 0.5, and 20 had a CDR ≥ 1. To discriminate between the participants with CDR 0 and those with CDR 0.5, the optimal cutoff score for the AD8 was 2. Including those with CDR ≥ 1 changed the best cutoff value to 3. In terms of the DSM-5 criteria, 59 participants had normal cognition, 28 had mild neurocognitive disorder, and 31 had major neurocognitive disorder or dementia. To discriminate between those with and without dementia, an AD8 cutoff value of 4 maximized the Youden index with more balanced sensitivity and specificity. Conclusion The AD8 may have different cutoff values depending on different purposes. Our findings suggest that the AD8 may perform better with a cutoff value of 4 to discriminate between those with and without dementia.